Why natural selection leads to complexity - Benzon, William L.; Hays, David G.; East-West Environment and Policy Institute; Southeast Asian Universities Agroecosystem Network; SUAN Information Support Service; Ford Foundation; East-West Center (1990)
While science has accepted biological evolution through natural selection, there is no generally agreed explanation for why evolution leads to ever more complex organisms. Evolution yields organismic complexity because the universe is, in its very fabric, inherently complex, as suggested by Ilya Prigogine's work on dissipative structures. Because the universe is complex, increments in organismic complexity yield survival benefits: (1) more efficient extraction of energy and matter, (2) more flexible response to vicissitudes, (3) more effective search. J.J. Gibson's ecological psychology provides a clue to the advantages of sophisticated information processing while the lore of computational theory suggests that a complex computer is needed efficiently to perform complex computations (i.e. sophisticated information processing).
Photocopy.
This document has been provided by EAPI as part of its SUAN Information Support Service. The goal of this service is to make current literature relating to human ecology and agroecosystems research available to scientists participating in the Southeast Asian Universities Agroecosystem Network. Partial funding for this service is provided by a Ford Foundation grant to the East-West Center.
Includes bibliographical references (page 40).
Keywords: Evolution